KLASIFIKASI KEEFEKTIFAN KEPEMIMPINAN DENGAN PENDEKATAN MODEL KEPEMIMPINAN TRANSFORMASIONAL DUA DIMENSI (Fokus Ekonomi, 2009)
The Bass Transformational Leadership Model has inspired the development of various transformational leadership researches. Several empirical researches indicate that there are problems concerning conceptual and methodology on the four constructs of behavior in the Bass Transformational Leadership Model. By reconceptualizing the four constructs, the author develop a new conceptual model that divide the leadership effectiveness into two main dimensions (charisma and intelligence). The result showed that, beside requiring emotional stimulation, subordinates also need intelligence stimulation. Thus, a transformational leader cannot only rely on charisma, but also has to be supported by a high degree of intelligence.